Recycled concrete aggregate for IBS component / Nur Athirah Mohamad Sakri - Mohamad Sakri, Nur Athirah (2018)
The demolition of an existing building and then replace it with a new one are becoming a trend. This trend leads to an increasing number of waste disposal which simultaneously reduce landfill spaces and pollute the environment. Besides, with rapid industralisation, the usage of aggregate is rapidly increasing due to the fact that it is one of the important materials for concrete. Hence, an alternative to overcome this issue is by using recycled concrete aggregate. The purpose of this study is to present an overview about the application of recycled concrete aggregate in construction project and to propose design mix of concrete with recycled concrete aggregate in Malaysia. Desk study on relevant research that is related to recycled concrete aggregate will be conducted and also a study on the critical review to relevant design mix of recycled concrete aggregate.The data and information will be tabulated to compare the most suitable design mix for local application . The expected findings of this study will be the design mix and method to conduct the experiment. Recycled concrete aggregate will not only help to preserve the natural resources but also reduce waste disposal as well as provide sufficient space for other waste at the landfill.